Los comerciantes del Consulado de México. La adecuación de sus mecanismos de control económico ante los cambios de la segunda mitad del siglo XVIII. El caso de las libranzas - Pérez Herrero, Pedro (1987)
The Bourbon reforms had begun to weaken the power of the merchants of the Consulado de México. The use of libranzas and other mechanisms allowed them to recover a central role in the economic of New Spain. Thus they were able to control domestic trade, to act as intermediaries between various economic sectors and monopolize foreign trade the essential basis for which was the exchange of silver for mercantile commodities.